2011
DOI: 10.1016/j.jsbmb.2010.11.005
|View full text |Cite
|
Sign up to set email alerts
|

CYP17 inhibitors for prostate cancer therapy

Abstract: Prostate cancer (PC) is now the second most prevalent cause of death in men in the USA and Europe. At present, the major treatment options include surgical or medical castration. These strategies cause ablation of the production of testosterone (T), dihydrotestosterone (DHT) and related androgens by the testes. However, because these procedures do not affect adrenal, prostate and other tissues androgen production, they are often combined with androgen receptor antagonists to block their action. Indeed, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(176 citation statements)
references
References 86 publications
1
164
0
8
Order By: Relevance
“…These findings have fostered an interest in CYP17A1 inhibition to deplete both intratumoral and extragonadal sources of steroid ligands (6,7). CYP17A1 is an essential enzyme for biosynthesis/production of steroidal hormones, and has both 17,20-lyase and 17a-hydroxylase activities (8)(9)(10). This pathway's importance in CRPC has been reinforced by positive phase III trials with abiraterone acetate (Zytiga; refs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings have fostered an interest in CYP17A1 inhibition to deplete both intratumoral and extragonadal sources of steroid ligands (6,7). CYP17A1 is an essential enzyme for biosynthesis/production of steroidal hormones, and has both 17,20-lyase and 17a-hydroxylase activities (8)(9)(10). This pathway's importance in CRPC has been reinforced by positive phase III trials with abiraterone acetate (Zytiga; refs.…”
Section: Introductionmentioning
confidence: 99%
“…Although type II ligands are typically viewed as P450 inhibitors due to stabilization of the low spin-state via coordination of the heme-iron to an aromatic nitrogen [69,82,83], studies have shown that in general, type II binding ligands have a higher affinity for the active site than similar but nitrogen-lacking substrates [84][85][86]. Moreover, a number of reports have demonstrated that P450s such as P450 3A4 can metabolize type II ligands, and in some cases to a greater extent than related type I ligand analogues [84,[87][88][89][90][91].…”
Section: Mammalian P450smentioning
confidence: 99%
“…Inhibition of the lyase activ- ity that leads to reduced androgen synthesis inhibits testosterone production and therefore the development of prostate cancer. Drugs that are effective in inhibition of CYP17A1 have been developed (21,22). Now that the enzyme structure cocrystallized with such inhibitors is available (17), even better drugs that would be able to inhibit the lyase activity without an effect on hydroxylase activity could probably be designed.…”
Section: P450-dependent Diseases Of Steroid Biosynthesis and Metabolismmentioning
confidence: 99%